2015
DOI: 10.1007/s00441-015-2283-8
|View full text |Cite
|
Sign up to set email alerts
|

Activating transcription factor 5 (ATF5) is essential for the maturation and survival of mouse basal vomeronasal sensory neurons

Abstract: Activating transcription factor 5 (ATF5) is a member of the CREB/ATF family of transcription factors, which is highly expressed in olfactory chemosensory tissues, the main olfactory epithelium and vomeronasal epithelium (VNE) in mice. The vomeronasal sensory neurons in the VNE detect pheromones in order to regulate social behaviors such as mating and aggression; however, the physiological role of ATF5 in the vomeronasal sensory system remains unknown. In this study, we found that the differentiation of mature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…Notably an incomplete ablation of basal VSNs have been also observed after loss-offunction of Ascl-1 and Ngn-1 (Cau et al, 2002), G-protein subunit Gγ-8 (Montani et al, 2013), loss-of-function of Gαo (Chamero et al, 2011), and the transcription factor ATF5 (Nakano et al, 2016). What underlies the varying responses and potential compensatory mechanisms to these mutations requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably an incomplete ablation of basal VSNs have been also observed after loss-offunction of Ascl-1 and Ngn-1 (Cau et al, 2002), G-protein subunit Gγ-8 (Montani et al, 2013), loss-of-function of Gαo (Chamero et al, 2011), and the transcription factor ATF5 (Nakano et al, 2016). What underlies the varying responses and potential compensatory mechanisms to these mutations requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, normal olfactory system development and olfactory function is important for social behavior (Silverman et al, 2010; Feierstein, 2012). It is reported that ATF5 -/- mice have olfactory system impairments (Wang et al, 2012; Umemura et al, 2015; Nakano et al, 2016). In ATF5 -/- mice, the size of the OB is reduced and the laminar structure of the OB is irregular (Umemura et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In ATF5 -/- mice, the size of the OB is reduced and the laminar structure of the OB is irregular (Umemura et al, 2015). Moreover, neuronal maturation is impaired in the MOE and VNE of ATF5 -/- mice (Wang et al, 2012; Nakano et al, 2016). ATF5 -/- male mice display reduced aggressiveness toward an intruder male mouse entering their territory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations